The ascension of a photo-poet : Garin Nugroho's quest for beauty / Maszalida Hamzah - Hamzah, Maszalida (UPENA, 2008)
This essay is part of the four poles of a meta-philosophical approach towards apprehending the films of acclaimed Indonesian film director Garin Nugroho as photo-poetry and himself, the photo-poet. It is the child of the first two poles being: Creation from Light and For All Time. The ascension of a photo-poet depicts his metaphysical journey into several realms, known and unknown as seen through the eye of the heart of the writer. It is through this journey that he captures, recaptures, discovers and rediscovers. This infinity of toiling, mingling and meditating process is the conditioning of his experiential quest into his' poesis,' an act of creation that makes him a photo-poet, rejuvenated at every moment in time.